Robust Vibration Control of Clamped Plate using Piezomaterial Ceramics - Kanwar, Preet Singh (My University, 2007)
Active vibration control (AVC) is not very old, although the control theory started to develope quite earlier, its applications were limited to the processes, which were quite slow. Slow chemical processes is the example, where the control theory showed its effectiveness in early days. Due to the lack of fast, dedicated processors, control theory remained only in theoretical frame, for active vibration control problems. Also the AVC is an interdisciplinary problem, in which use of intrumentation and control field is extensively involved. So the practical utility of AVC remained in research domain only, for a long period of time. With the emmergence of embedded automation, fast processors became the practical reality. Some dedicated software firms, collaborated with hardware firms and extended the technology of ‘computer based instrumentation’ or ‘computer based measurements’. Interdisciplinary gap is thus reduced. Using these ‘computer based instrumentation’ techniques along with ‘real time engines’, AVC emerged as a practical reality few years back. Also with the development of piezoelectric ceramics, ‘Intelligent’ or ‘smart’ structures using low cost sensors and actuators, mounted on the surface of the flexible structure, AVC came into existance. Combining all these technologies, the practical applications of AVC are now increasing day by day. Several advanced applications, such as those in jet fighters, automobiles and spacecrafts, require structures that are highly strong, lightweight and possess high structural damping property. A great difficulty is faced in the design of such structures due to the fact that the reduction in weight results in low rigidity and poor vibration characteristics. Unless the vibration is effectively controlled, it may destabilize the system and may, very often, result in complete failure of the system. Therefore, there is need to develop structures that are equipped with suitable vibration control features. Smart structure technology using robust control system may provide a solution to this problem. These structures use piezoelectric materials, electro-rheological (ER) fluids and shape memory alloys as sensors and actuators for providing effective vibration control. Active vibration control requires high sampling rate and fast processors for doing control. Using the computer based measurements active vibration control is now a practical reality. A detailed literature survey carried out for setting objectives for the present work suggests further work on the development of an Robust controller for estimating the parameters of a flexible structure and then using these parameters for the design of an effective controller. So, the present work deals with a rectangular steel plate modeled in a cantilever configuration with surface bonded with piezoelectric patches. The study uses ANSYS (vs 5.6) software to derive the finite element model of the steel plate. By using the results from ANSYS a single – input/single-output H∞ controller is designed to suppress the vibrations due to the first two flexural modes of the plate. And it has been shown that the designed controller guaranties robust performance.
Keywords: Active Vibration Control; Cantilever; Electro-Rheological Fluids